On the Lathrobium fauna of the Luoxiao Mountains, Central China - Peng, Zhong; Li, Li-Zhen; Zhao, Mei-Jun (Zootaxa, 2016)
Thirteen species of Lathrobium Gravenhorst, 1802 are recorded from the Luoxiao Mountains, Central China, all of them micropterous and locally endemic. Eight species are described and illustrated: L. bamianense Peng & Li sp. n., L. fumingi Peng & Li sp. n., L. jinyuae Peng & Li sp. n., L. jiulingense Peng & Li sp. n., L. shuguangi Peng & Li sp. n., L. taiye Peng & Li sp. n., L. yangshimuense Peng & Li sp. n., and L. yipingae Peng & Li sp. n. Five probably undescribed species remain unnamed. Including the new taxa, 219 Lathrobium species are currently known from mainland China.